(untitled) - Singh, R. Paul. (Amsterdam,Boston, 2009)
The fourth edition of this leading textbook presents the engineering concepts and unit operations used in food processing in a classroom-proven and unique blend of principles with applications. Describing the application of a particular principle followed by the quantitative relationships that define the related processes, each chapter also includes solved examples and problems to evaluate reader comprehension.
Tổng kê vật chất và năng lượng,Các quá trình và thiết bị ứng dụng trong công nghệ sau thu hoạch,Nhiệt kỹ thuật
Keywords: Food industry and trade.,Thương mại và công nghệ thực phẩm